Bodhisattva in “chorus Nok Ka Nam" of the Ritual Nora Rong Kru Southern Thailand - Kongchim, Channarong (Journal of MBU Humanities, 2024)
This article aims to study the role of Bodhisattvas. and the essence that appears in the “chorus Nok Ka Nam” in the ritual Nora Rong Kru Southern Thailand The results of the research (1) on the role of the Bodhisattva, it was found that the Nok Ka Nam was a chorus that mentioned the Bodhisattva according to the views of the villagers in the south. When considering the nature of the Jataka It was found that the Bodhisattva was the main character, playing a role in upholding morality to prevent the characters from behaving in a wrong way. (2) Essence of the chorus, it was found that Nok Ka Nam Focus on teaching about gratitude not neglecting teachers and being a person who adheres to the truth.